China's English a history of English in Chinese education - Adamson, Bob (Asian Englishes today., 2004)
"This book traces the history of English education in the People's Republic of China from 1949 to the present day. It uses the junior secondary school curriculum as the means to examine how English curriculum developers and textbook writers have confronted the shifting ambiguities and dilemmas over five distinct historical periods. The study of the processes of curriculum development and the products such as syllabi and textbooks offers insights into the construction of an 'official' English, as well as what was considered as acceptable content in English. This book addresses fundamental and significant questions concerning the English promoted in China, namely its characteristics; its changes over time and explanations for such changes; and the kind of content that has been viewed as appropriate for textbooks. To investigate these issues, the analysis draws on qualitative and quantitative data, such as interviews with principle stakeholders and analysis of the syllabus and recommended textbooks. Specifically, it looks at the choice and organization of linguistic components, and the orientation and messages of the curriculum"--Dustjacket.